(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2014)
This paper shows that Szasz (1) opposed the presumption of illness; (2) duelled with dualism; (3) researched the history of ’hysteria’; (4) perceived its profound paradigmatic potential; (5) confirmed the compassion of the confused; (6) denounced ’mental health’ and ’anti-psychiatry’; (7) rejected the role of ’physician’ to the ’mentally ill’.